Case report: Combinations of immune checkpoint inhibitor, chemotherapy, and hyperthermia therapy avoid lymphatic recurrence in cholangiocarcinoma - Chang, Heng-Jui; Ke, Chiao-Hsu; Wang, Yu-Shan (Frontiers in Oncology, 2024)
Cholangiocarcinoma is a malignancy known for its aggressiveness and limited treatment options. The malignant tumor behaviors include intrahepatic recurrence, regional lymph node (LN) metastasis, peritoneal carcinomatosis, and lung metastasis. Herein, we reported a case of lymphatic recurrence in an intrahepatic cholangiocarcinoma patient after surgery, adjuvant concurrent chemoradiotherapy (CCRT), who experienced a remarkable response to a combination therapy. However, the patient failed to undergo radiotherapy or other invasive local therapy and therefore received Opdivo (nivolumab) in combination with chemotherapy (FOLFOX) and modulated electro-hyperthermia. Notably, after these medical interventions, this patient had a complete response (CR) to treatments, in which no lymph node metastasis occurred, and a significantly decreased tumor marker, CA 19-9, level was found. This case highlights the potential of multiple anti-tumor therapies, including immune checkpoint inhibitors, chemotherapy, and hyperthermia, in managing challenging cholangiocarcinoma cases.